Serum sPD-1 as a marker of T cell exhaustion in ART-naïve, ART-experienced, and intestinal parasite co-infected HIV-positive adults at the university of Gondar comprehensive specialized hospital, Northwest Ethiopia, 2024 - Tadelo Wondmagegn; Wubet Birhan; Eseye Derb; Mulualem Lemma; Hana Yohannes; Degsew Ewunetie Anteneh; Alembante Bazezew; Kebebe Tadesse; Bewuketu Belete Alemu (BMC Infectious Diseases)
Abstract Background Human Immunodeficiency Virus (HIV) remains a significant global health challenge despite advancements in prevention and treatment. It impairs immune function and leads to T-cell exhaustion, driven by sustained expression of the immune checkpoint receptor PD-1, which exists in membrane-bound and soluble forms. While serum soluble programmed death protein 1 (sPD-1) may serve as a marker for immune exhaustion, its role in antiretroviral therapy (ART) and intestinal parasite (IP) co-infections remains underexplored, especially in developing countries like Ethiopia with high HIV and IP prevalence. Hence, this study investigates sPD-1 levels in ART-naïve, ART-experienced, and IP co-infected HIV-positive adults at the University of Gondar Comprehensive Specialized Hospital (UOGCSH), Northwest Ethiopia. Methods An institution-based cross-sectional study was conducted among 89 HIV-positive patients from the 1st of May to the 30th of June, 2024, at the UOGCSH. Socio-demographic, clinical, and laboratory data were extracted from a previous project assessing intestinal parasite prevalence in the same population. Quantitative ELISA was used to measure the serum levels of the T cell exhaustion marker, sPD-1. The median serum sPD-1 levels were compared using Kruskal-Wallis and Mann-Whitney U tests. All statistical analyses were conducted using Stata 14 and R version 4.4.0 software. Finally, statistical significance was declared at a p-value of < 0.05. Results Of 89 participants, 64 (71.9%) were ART-experienced, and 43 (48.3%) were IPco-infected. The median serum sPD-1 concentration was significantly higher in the ART-naive group (141.7 pg/mL) compared to ART-experienced counterparts (92.5 pg/mL), (p-value = 0.004). The median sPD-1 levels in the IP co-infected group (117.2 pg/mL) were also significantly higher compared to the IP HIV mono-infected group (77.2 pg/mL), (p-value = 0.0001). Moreover, the presence of IP co-infection significantly increased sPD-1 levels in the ART-experienced group based on a stratified analysis. Conclusion Patients who were ART-naïve, co-infected with intestinal parasites, and had high viral loads exhibited significantly higher levels of sPD-1, suggesting a possible association with increased immune exhaustion. These findings indicate that sPD-1 may have potential as a biomarker for monitoring immune status in HIV-positive individuals. However, further longitudinal and interventional studies are needed to determine its clinical utility in guiding therapeutic decisions. Clinical trial registration Not applicable.